C-Fos Digital Expression Analysis in Human PapillomavirusRelated Oral Squamous Cell Carcinoma - Chrysovergis, Aristeidis; Papanikolaou, Vasileios; Mastronikolis, Nicholas; Spyropoulou, Despoina; Adamopoulou, Maria; Tsiambas, Evangelos; Ragos, Vasileios; Peschos, Dimitrios; Roukas, Dimitrios; Stavraka, Chara; Niotis, Athanasios; Kyrodimos, Efthymios (Asian Pacific Journal of Cancer Biology, 2021)
Background: Fos Proto-Oncogene (c-Fos) represents a well analyzed gene involved in solid malignancies’ development and progression. The corresponding protein forms heterodimer with c-jun, a strong transcription factor. C-Fos/c-Jun complex influences critically the intracellular signal transduction to the nucleus. Our aim was to detect and evaluate c-Fos protein expression patterns in oral squamous cell carcinomas (OSCC) tissues. Materials and Methods: Fifty (n=50) formalin-fixed, paraffin-embedded primary OSCCs tissue sections were used. Immunohistochemistry and digital image analysis were implemented for identifying and evaluating c-Fos protein expression levels, respectively. Results: C-Fos protein over expression (moderate to high imunostaining intensity values) was observed in 28/50 (56%) tissue cores, whereas low expression rates were detected in the rest of the examined cases (22/50- 44%). C-Fos overall expression was strongly associated with the stage and grade of the examined tumors (p=0.014, p=0.003, respectively) and also with Human papillomavirus (HPV) persistent infection (p=0.004). c-Fos up regulation is frequently observed in OSCCs. Conclusion: C-Fos high expression levels are correlated with an aggressive phenotype (advanced stage/lymph node metastasis) in patients with OSCC, especially in HPV positive cases, especially High Risk subtypes. Due to its elevated oncogenic activity, c-Fos should be a target for novel therapeutic strategies in OSCC combined or not with other oncogenes involving in signaling transduction pathways.